Inuit Country Food and Health during Pregnancy and Early Childhood in the Circumpolar North: A Scoping Review - Amy B. Caughey; Jan M. Sargeant; Helle Møller; Sherilee L. Harper (International Journal of Environmental Research and Public Health, 2021)
Inuit communities in the Circumpolar North have experienced a nutrition transition characterized by the decreased intake of culturally important, nutrient-rich traditional food (country food), and an increased intake of market food, resulting in concerns over reduced diet quality and emerging chronic diseases. Nutrition in early life is critical for development, may influence health risks in later life, and is an important concern for Inuit community health. The goal of this scoping review was to characterize the nature, extent, and range of the published literature on Inuit country food and health in pregnancy and childhood. A search string was developed and applied to three databases, followed by title and abstract screening and full text review. Articles published between 1995 and 2019 were included, and data were extracted and summarized descriptively. The number of articles generally increased over time, despite the unequal geographic distribution of articles. The majority of the articles focused on environmental contaminants, and one-quarter described nutrient adequacy. Few articles described food security or food safety in pregnancy, and the most utilized quantitative methods. Gaps in understanding of country food use in pregnancy and early childhood highlight areas of future research to support public health policy for this population. Given the critical role of good nutrition in early life and the important contribution country food makes to diet quality for Inuit, further understanding of this interface is warranted.